The crystalline state of rubrene materials: intermolecular recognition, isomorphism, polymorphism, and periodic bond-chain analysis of morphologies. (4th April 2022) - Moret, Massimo; Gavezzotti, Angelo
Abstract : Crystal structure analysis and lattice energy calculations of 33 rubrenes provide a background for new ideas on synthesis and planning of transport properties. Abstract : A survey of all crystal structures of rubrene materials in the Cambridge Structural Database is presented. Although the chemical substitution landscape is wide, hydrogen bonding functionalities are absent. Recognition motifs frequently found in crystals are the "slipped-cofacial" molecular pairing, and herringbone or purely translational 3-D propagation. Packing modes are classified in terms of structure determinants, cohesive energies of pairs of molecules in closer contact computed by the CLP atom-atom potential field. In these terms, crystal isomorphism with different chemical substitution is quantitatively assessed. Polymorphs are relatively few, perhaps due to poor solubilities that hamper crystallization screenings. True polymorphs are also identified by structure determinant patterns, and a new polymorph of the di- p -nitrophenyl derivative has been prepared and characterized by X-ray diffraction. Crystal morphologies of selected rubrenes have been predicted by Hartman's Periodic Bond Chain approach using PIXEL attachment energies; there is good agreement with experimental morphologies of crystals grown by sublimation. The good results obtained by CLP and PIXEL show promise for a computationally cheap access to lattice energies and morphology prediction. In general, from our overview it looks like sensitive spots in the driving forces for rubrene packing are the 4-substitution sites at the lateral rings, with substituents of moderate steric bulk. Peripheral substitution at the tetracene core seems to be less relevant. Our survey provides a structural background fostering new ideas on the synthesis and planning of physical properties of rubrenes.